APLIKASI MODEL SUPERVISI KEPERAWATAN MOSCKA (MODEL SUPERVISI: COACHING KEPERAWATAN) PADA MANAJER PERAWAT - Rahayu, Candra Dewi (Jurnal Ilmiah Kesehatan, 2020)
The coaching guidance method is a way to achieve the best performance for individuals and organizations. Coaching unlocks one's potential to maximize performance. One of the coaching methods is MOSCKA (Model Supervisi: Coaching Keperawatan) Objective: supervision effectiveness with MOSCKA (Model Supervisi: Coaching Keperawatan) Method: quantitative research with quasi experimental pre-post test control group design with sample collection technique using consecutive sampling Results : The results of the Repeated Anova statistical test for Nursing Coaching Supervision showed that the p-value in the intervention group was 0.02 at = 0.05 and in the control group was 0.50 at = 0.0. Conclusions and Suggestions: There is a difference in the coaching ability of the head of the room before and After the intervention, it is hoped that this research can contribute to the field of science, especially management